COMPARATIVE ANALYSIS OF FARMERS’ MARKETS IN THE HUNGARIANTRANSDANUBIAN REGION - Nóra Gombkötö (Annals of the Polish Association of Agricultural and Agribusiness Economists)
A farmer’s market, as a type of short supply chain, can solve many problems concerning long--distance transport. In this sales form, physical distance is reduced between the producer and the consumer.Furthermore, personal relationships and trust can also be established between these two actors. In addition,it provides small producers with the opportunity to produce and sell local, high-quality foods, andconsumers are able to enjoy delicious, mostly locally-sourced, organic food products. Farmers’ marketsare becoming an increasingly popular sales channel in Hungary. While in 2010 there were 100, in 2014there were around 200 farmers’ markets; in 2017, their number increased to more than 250. The NationalRural Development Programme also encourages the sale of local products in this form. In this paper, aquestionnaire survey was conducted among producers in the largest farmers’ markets of the TransdanubianRegion in Hungary. The findings were used to analyze the farmers’ market features of the region.